Selection of bacteria and fungi for control of soilborne seedling diseases of maize - Tobias Pfeiffer; Astrid von Galen; Petra Zink; Sebastian Hübner; Ada Linkies; Dieter Felgentreu; Jannika Drechsel; Tim Birr; Olaf Röder; Mathias Kotte; Kristin Dietel; Helmut Junge; et al. (Journal of Plant Diseases and Protection, 2021)
Plant-based screening experiments were conducted with the aim of identifying biocontrol bacteria and fungi for seed treatment of maize. Candidate microorganisms were evaluated for their protective effects against soilborne infections by species of Fusarium , Globisporangium (syn. Pythium ) and Rhizoctonia. The microorganisms tested were bacteria and fungi from maize roots or other sources, including some active microbial components of commercial biocontrol products. Due to the method of isolation chosen, the majority of bacteria from maize roots were spore formers, most of them species of the genera Bacillus, Brevibacillus and Paenibacillus . In pot tests with the potting substrate inoculated with F. culmorum, the level of control provided by seed treatment with the most efficacious bacterial and fungal isolates was comparable or close to the chemical reference seed treatment thiram. The most effective bacteria were species of Pseudomonas , Burkholderia and Streptomyces . Among a subset of approx. 100 bacteria studied, the in vivo and in vitro activities against F. culmorum were only weakly correlated, although some strains deviated from this pattern. The most effective fungi were two strains of Clonostachys rosea and isolates of Trichoderma . The latter and a strain of Gliocladium virens provided also protection against R. solani . Activity against Globisporangium ultimum was recorded for one isolate of Trichoderma and the two strains of C. rosea. A reduction in the impact of seedborne F. culmorum was also observed after seed treatment with two strains of F. oxysporum f. sp. strigae. The results are discussed in relation to previous reports on rhizosphere bacteria of maize and their use in biocontrol of plant pathogens or for plant growth promotion.